Identidad étnica y redes personales entre jóvenes de Sarajevo - Claudia Aguilar; José Luis Molina (Araucaria)
After fieldwork conducted among young people in Sarajevo, we found arelation between the discourses sustained by them and the ethnic categories theyuse to classify people and to identify themselves. Also we have found that peopleself-affiliated as Bosnians play an important role in the network of multiethnicrelationships, in which strong ties, surprisingly, are still very important. Finallywe found a relationship between the composition of personal networks and theethnic discourses that are maintained.